Penyuluhan Online Mengenai Premenstrual Syndrome (PMS) Pada Remaja Di Smpn 1 Cikarang Utara - Rizky Fitr Andini; Dewi Agustin; Ikha Prastiwi; Zuriati; Seli Nur Iseli; Aulia Chandra Dewi; Yuyun Antika sari (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2021)
Background: According to the Youth Friendly Health Service (PKRR) in 2005, it was stated that women's problems in Indonesia are around 3 problems regarding menstrual disorders (38.45%), nutritional problems related to anemia (20.3%), learning disorders (19.7% ), psychological disorders (0.7%), and obesity problems (0.5%). Menstrual disorders are a major problem for women in Indonesia. Purpose: The purpose of this activity is to increase the knowledge of seventh grade students at SMP Negeri 1 Cikarang Utara about reproductive health related to premenstrual syndrome (PMS) in adolescents. Method: this reproductive health counseling for adolescents was carried out online using Google Meet with 21 participants. The method used is lecture, question and answer Results: there is an increase in knowledge before and after health counseling and during the counseling the participants are cooperative and actively ask questions Conclusion: Teenage girls who experience premenstrual syndrome (PMS), teenagers need to increase their knowledge by seeking information through print or electronic media and take good care so that they can reduce the symptoms of premenstrual syndrome and feel better